2023
DOI: 10.1093/ofid/ofad156
|View full text |Cite|
|
Sign up to set email alerts
|

Hyponatremia as a Predictor of Cryptococcal Meningitis and Death Among Asymptomatic Persons With HIV and Cryptococcal Antigenemia

Abstract: Among persons with HIV-associated cryptococcal meningitis serum hyponatremia is a risk factor for mortality; however, the role of hyponatremia in persons with asymptomatic cryptococcal antigenemia is unknown. We found that serum hyponatremia <130 mmol/L is an independent risk factor for progression to meningitis and death in asymptomatic persons with cryptococcal antigenemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Persons with CrAg lateral flow assay (LFA) titers ≥1:160 have a ∼3-fold higher risk of meningitis or death at 6 months in a Uganda study [ 10 ], and similar findings have been found in Ethiopia, South Africa, and Tanzania [ 13–15 ]. A few additional predictors have previously been identified including hyponatremia and lower body mass index [ 16 , 17 ]. However, a thorough understanding of the landscape of risk predictors and how they interact with each other is needed to best design interventions to mitigate morbidity and mortality.…”
mentioning
confidence: 99%
“…Persons with CrAg lateral flow assay (LFA) titers ≥1:160 have a ∼3-fold higher risk of meningitis or death at 6 months in a Uganda study [ 10 ], and similar findings have been found in Ethiopia, South Africa, and Tanzania [ 13–15 ]. A few additional predictors have previously been identified including hyponatremia and lower body mass index [ 16 , 17 ]. However, a thorough understanding of the landscape of risk predictors and how they interact with each other is needed to best design interventions to mitigate morbidity and mortality.…”
mentioning
confidence: 99%